Entertainment in air raid shelter, South London 1940 (1940)
1940 1939-1945 "Entertainment in air raid shelter, South London 1940" [HFR0217], 1940 The Bermondsey Shelter Council for Social Activities was set up by the local council, churches and the Bermondsey Repertory Company not only to improve environmental conditions in the borough's shelters but also to maintain the morale of local people. Whist drives, dances, films, talent competitions and evening classes were organised and the Council for the Encouragement of Music and the Arts (CEMA) also provided theatre groups and professional musicians. This article is from Local Government Service, the journal of the National Association of Local Government Officers [ NALGO ] December 1940.